The Criminal justice system in Northern Ireland - Carr, Nicola (Oxford University Press, 2017)
As with any country, crime and justice and the contours of criminal justice have to be situated within the particular historical, social, and political context. Nowhere is this truer than in Northern Ireland, where the criminal justice system that has emerged has been shaped by a violent political conflict which spanned over three decades (from the late 1960s to the late 1990s). In the transition to peace, the reform of criminal justice agencies has been central—to a wider project of state legitimacy. This chapter begins with a brief historical overview of Northern Ireland and some of the key ways in which various aspects of criminal justice have been impacted by the Troubles. It then provides a brief overview of the current system of government before outlining the existing criminal justice context in Northern Ireland and the key criminal justice agencies involved in the criminal justice system. This includes a particular focus on the police, probation, prisons, the youth justice system, and criminal justice oversight bodies. The challenges of the transition from conflict for the criminal justice system, the ongoing reform, and the continued legacies of the conflict are explored.